2023
DOI: 10.23822/eurannaci.1764-1489.241
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative comparison of allergen component-specific to birch and grass analyzed by ImmunoCAP assay and Euroline immunoblot test

Abstract: Background: In the diagnostic work up of allergy, determining allergen component-specific immunoglobulin E (IgE) is important for diagnosis, prognosis and choice of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Several researchers found that the sensitivity of a population depends on the local flora (and pollen), concluding that if a plant species is widespread in a geographical area, the population can tolerate a higher concentration of this pollen before the symptoms appear [27,28]. Different authors pointed out that the presence of a certain plant species affects the tolerance of the population and the appearance of symptoms, such as Betula [29,30], Phleum pratense [30] or Dactylis glomerata [31].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers found that the sensitivity of a population depends on the local flora (and pollen), concluding that if a plant species is widespread in a geographical area, the population can tolerate a higher concentration of this pollen before the symptoms appear [27,28]. Different authors pointed out that the presence of a certain plant species affects the tolerance of the population and the appearance of symptoms, such as Betula [29,30], Phleum pratense [30] or Dactylis glomerata [31].…”
Section: Introductionmentioning
confidence: 99%